Pengaruh Promosi Penjualan dan Ulasan Produk terhadap Keputusan Pembelian Online Pengguna E- Commerce Lazada Pada Masyarakat di Kecamatan Plumpang Kabupaten Tuban - Khofifah Indra Parawansa; Sarjita Sarjita (Jurnal Bisnis, Manajemen, dan Akuntansi, 2023)
The aim of this research is to find out the impact of sales promotion and product reviews partially or simultaneously on online purchasing decisions of Lazada e-commerce users on the community in Plumpang district of Tuban. A type of quantitative research with a sample of 100 samples. The types of data used are primary and secondary data, obtained from the dissemination of surveys and library studies. The data testing in this study is validity test, reliability test, classical assumption test consisting of normality, multicolinearity, and heteroskedastisity tests, then double linear analysis test, t test (partial), F test (simultaneous), correlation test and determination test processed using computer software SPSS version 20.0 for windows. The results of the research showed that partly the variables of sales promotion and product reviews influenced the purchase decision, while the variable of product quality did not influence the online purchase decision of e-commerce in the community in Plumpang district of Tuban. In addition, price variables, product reviews and transaction security contribute to the purchase decision. Keywords: sales promotions, product reviews, purchase decisions